(untitled) (Open International Journal of Informatics, 2025)
The assignment problem in operations research is a method to assign a set of agents for a set of tasks to minimize cost or maximize profit. The method proves to be beneficial in various industries and has been used extensively, including in the development of e-hailing mobile applications. In this research, a real-life example application of an assignment problem using the Hungarian method was used to solve the assignment of e-hailing drivers to customers and patients to beds in the healthcare industry. The Hungarian method calculation was also checked with Excel Solver to find the objective function, subject to well-defined constraints. The result of this study shows the optimized matchmaking of the shortest distance between the e-hailing driver and the customer. Another example, minimizing the cost of total expense in assigning patients to specific beds in a hospital. This study also highlighted findings by other researchers using the assignment problem method could be used as a foundation to develop a new heuristics-based method, especially in healthcare management.